KNOWLEDGE SHARING PADA DOSEN STIE PEMBANGUNAN TANJUNGPINANG - Evita Sandra; Maryati Maryati; Bunga Paramita (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Universities as service providers in higher education are highly dependent on humen capital as intangible assets attached to human resources (HR). HR in universities is required to have knowledge and skills and abilities in the creation of knowledge assets, for that universities need to manage their knowledge and intellectuals and encourage individuals who are in it to share knowledge (knowledge sharing) to develop competence and expand knowledge. This research aims to find out the factors that determine the most determining knowledge sharing behavior at lecturers of STIE Pembangunan Tanjungpinang. Population in the study as many as 75 lecturers who mastered courses in the even semester of the even semester year 2020-2021. A sample of 67 people using purposive sampling with ktriteria respondents had a working life of more than one year. Data analysis is done using Structure Equation Modeling (SEM). The results showed that the factor that most influences lecturers to choose knowledge sharing is the ability to share.